2019
DOI: 10.1017/jfm.2019.232
|View full text |Cite
|
Sign up to set email alerts
|

Quasistatic magnetoconvection: heat transport enhancement and boundary layer crossing

Abstract: We present a numerical study of quasistatic magnetoconvection in a cubic Rayleigh-Bénard (RB) convection cell subjected to a vertical external magnetic field. For moderate values of the Hartmann number Ha (characterising the strength of the stabilising Lorentz force), we find an enhancement of heat transport (as characterised by the Nusselt number N u). Furthermore, a maximum heat transport enhancement is observed at certain optimal Ha opt . The enhanced heat transport may be understood as a result of the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…In the future, it will be of interest to extend the study to the 3-D case, to allow for a one-to-one comparison with experiment. Following the comparative study of Chong et al (2017) and Lim et al (2019), it is also desirable to investigate further turbulent flows with different stabilizing forces, to get an even more complete understanding of various stabilizing-destabilizing flow systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, it will be of interest to extend the study to the 3-D case, to allow for a one-to-one comparison with experiment. Following the comparative study of Chong et al (2017) and Lim et al (2019), it is also desirable to investigate further turbulent flows with different stabilizing forces, to get an even more complete understanding of various stabilizing-destabilizing flow systems.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn improves the convective heat transport and compensates the effect of an overall slower flow magnitude. In simulations of magnetoconvection at Pr ∼ 8, Lim et al (2019) even found an increase of Nu for an optimal Ha. Such an improvement of the transport properties is generally associated with the cross-over of the viscous and the thermal boundary layer (BL) (Chong et al 2017;Lim et al 2019).…”
Section: Global Transport Propertiesmentioning
confidence: 92%
“…The most significant discrepancies between the two datasets appear at higher values of ) data shows a lower slope in comparison with the simulations (both P r = 0.025 and P r = 1). Because this difference is largest at higher values of Ra, it might be due to, as suggested by Cioni et al (2000), the formation of a large-scale circulation in the experimental apparatus due to the eventual loss of magnetic constraint and flow anisotropy (Vogt et al 2018a;Lim et al 2019). Additional studies in cylindrical geometry are necessary to quantify this effect in more detail.…”
Section: The Influence Of the Prandtl Numbermentioning
confidence: 96%